Modified hard carbon material, sodium ion battery based on modified hard carbon material, battery negative electrode material and method

Through the preparation method of modified hard carbon materials, the cross-linking network structure and dopants are used to improve the reversible specific capacity and rate performance of the negative electrode of the sodium ion battery, and the problem of poor performance of existing hard carbon materials is solved.

CN119461316APending Publication Date: 2025-02-18SHAANXI COAL & CHEM TECH INST
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411602427.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing hard carbon materials exhibit poor reversible specific capacity and rate performance in the negative electrode of sodium ion battery, limiting their further development.

Method used

Modified hard carbon material was prepared by mixing organic matter, curing agent, solvent and dopants and subjecting to heat curing and high-temperature carbonization. This method forms a crosslinking network structure, inhibits the orientation arrangement of graphite sheets, and broadens the layer spacing through dopants to increase sodium storage sites.

Benefits of technology

The reversible specific capacity and rate performance of the negative electrode of sodium ion battery are improved, and the problem of poor performance of existing hard carbon materials is solved, and negative electrode materials with stable structure and low specific surface area are obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461316A_ABST
    Figure CN119461316A_ABST
Patent Text Reader

Abstract

The invention discloses a modified hard carbon material, a sodium ion battery based on the modified hard carbon material, a battery negative electrode material and a method, and belongs to the technical field of energy storage materials. According to the preparation method disclosed by the invention, an organic matter is taken as a precursor and is crosslinked and cured with a curing agent, so that a crosslinked network structure can be formed, and directional arrangement of graphite flake layers is inhibited in a subsequent carbonization process. The graphitization amorphous degree of the hard carbon can be controlled by regulating and controlling the polymerization degree, so that a large number of micropores are formed, and certain structural stability is achieved. In addition, through doping, the interlayer spacing of hard carbon can be widened, intercalation / deintercalation of sodium ions is promoted, meanwhile, defect sites are introduced, sodium storage sites are increased, and the specific capacity of the negative electrode is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of energy storage materials, and in particular relates to a modified hard carbon material and a sodium ion battery, a battery negative electrode material and a method based thereon. Background Art

[0002] Currently, as the main application in the field of new energy, the demand for lithium-ion batteries is increasing. However, due to the shortage of lithium resources, uneven distribution and difficulty in refining, the price of lithium battery raw materials has risen. It is necessary to develop new low-cost alternative battery technologies.

[0003] Sodium-ion batteries have similar working principles to lithium-ion batteries, and sodium resources are abundant, low-cost, and environmentally friendly. Therefore, sodium-ion batteries have received widespread attention and are expected to be used as a supplementary product to lithium-ion batteries in large-scale energy storage power stations and low-speed electric vehicles. Since the radius of sodium ions is larger than that of lithium ions, when sodium ions are embedded in graphite sheets, the binding energy of the sodium ion-graphite embedding reaction ΔG>0 makes it difficult for sodium ions to be effectively embedded and removed between graphite layers. Therefore, graphite as a negative electrode for sodium-ion batteries has low capacity and poor cycle stability. The development of high-performance negative electrode materials is a key link in the industrialization of sodium-ion batteries.

[0004] The main research directions of negative electrode materials for sodium ion batteries include carbon-based materials, metal compounds, alloy materials, organic materials, etc. Among them, carbon-based materials have the characteristics of low working voltage, stable structure (small volume phase change), low cost, safety and non-toxicity, etc., and relying on the development background of lithium battery graphite negative electrode, carbon-based materials have sufficient research and development experience, and are currently recognized as the earliest negative electrode materials for sodium ion batteries that can be commercialized.

[0005] In recent years, hard carbon has been considered as a promising anode material for sodium-ion batteries due to its large interlayer spacing, good structural stability and high reversible capacity. However, the existing hard carbon materials have limited their further development in the field of sodium-ion battery anodes due to their poor reversible specific capacity and rate performance. Summary of the invention

[0006] The purpose of the present invention is to provide a modified hard carbon material and a sodium ion battery, a battery negative electrode material and a method based thereon, so as to solve the technical problem that the existing hard carbon materials have poor reversible specific capacity and rate performance.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] The invention discloses a method for preparing a modified hard carbon material, comprising the following steps:

[0009] After mixing the organic matter, the curing agent, the solvent and the dopant, the mixture is heated and cured to obtain a hard carbon precursor;

[0010] The hard carbon precursor is subjected to heat treatment and high-temperature carbonization treatment in sequence to obtain a modified hard carbon material.

[0011] Furthermore, the organic matter is one or more of acrylic resin, phenolic resin, epoxy resin, furfural resin, urea-formaldehyde resin, sugar alcohol resin, polyurethane, polyethylene, polyvinyl chloride, polyvinyl chloride alcohol, polycarbonate, polytetrafluoroethylene, polyvinylidene fluoride, polyacrylonitrile, styrene-butadiene rubber, polyethylene oxide, polymethyl acrylate and polyimide.

[0012] Furthermore, the curing agent is one or more of hexamethylenetetramine, 2,4,6-tris(dimethylaminomethyl)phenol, benzyldimethylamine, maleic anhydride, bismaleic anhydride, hexamethylenediamine and metaphenylenediamine.

[0013] Furthermore, the solvent is one or more of water, isopropanol, ethanol, ethylene glycol, and n-butanol;

[0014] The dopant is one or more of a metal element, a non-metal element, a metal compound and a non-metal compound;

[0015] The metal element is one or more of copper, magnesium, manganese, tin, cobalt and nickel, and the non-metal element is one or more of silicon, sulfur, phosphorus and boron; the metal compound is one or more of tin oxide, cobalt oxide, nickel oxide, manganese oxide, sodium phosphate, sodium dihydrogen phosphate, tin acetate, tin chloride, manganese chloride, cobalt carbonate, copper hydroxide, cobalt hydroxide, tin hydroxide and nickel hydroxide; the non-metal compound is one or more of silicon dioxide, phosphorus pentoxide, boric acid, silicic acid, phosphoric acid, ammonium dihydrogen phosphate, ammonium phosphate and ammonium sulfate.

[0016] Furthermore, the mass ratio of the curing agent to the organic matter is 1:(1-20); the mass ratio of the solvent to the organic matter is 1:(1-8); the mass ratio of the dopant to the organic matter is 1:(20-500);

[0017] The temperature of the heating and curing treatment is 120-220°C and the time is 1-24h;

[0018] After the heating and curing, the product is screened to obtain a hard carbon precursor.

[0019] Furthermore, the heat treatment is carried out in an inert atmosphere; the temperature of the heat treatment is 400 to 800° C., the heating rate is 1 to 10° C. / min, and the heat treatment time is 1 to 12 hours;

[0020] The inert atmosphere is one of argon and nitrogen.

[0021] Furthermore, a grinding process is also included between the heat treatment and the high-temperature carbonization treatment; the temperature of the high-temperature carbonization treatment is 1000-1700°C, the heating rate is 1-10°C / min, and the duration of the high-temperature carbonization treatment is 1-8h.

[0022] The invention also discloses a modified hard carbon material prepared by the preparation method.

[0023] The present invention also discloses a sodium ion battery negative electrode material based on the modified hard carbon material. The sodium ion battery negative electrode material is obtained by coating a sodium ion battery negative electrode slurry obtained by mixing the modified hard carbon material, a conductive additive and a binder on a current collector and drying the mixture.

[0024] The mass ratio of the modified hard carbon material, the conductive additive and the binder is 8:(1-4.5):(0.5-1);

[0025] The conductive additive is one of Super P, acetylene black or Ketjen black; the adhesive is one of polyacrylic acid or sodium carboxymethyl cellulose.

[0026] The present invention also discloses a sodium ion battery based on the above sodium ion battery negative electrode material, wherein the electrolyte of the sodium ion battery consists of a sodium salt and an organic solvent;

[0027] The sodium salt includes at least one of NaBF4, NaFSI, NaClO4, NaTFSI and NaPF6;

[0028] The organic solvent includes at least one of ethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethyl carbonate, diethyl carbonate, propylene carbonate, and ethylene carbonate.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The invention discloses a preparation method of a modified hard carbon material. An organic matter is used as a precursor. Through cross-linking and curing with a curing agent, a cross-linked network structure can be formed. In the subsequent carbonization process, the directional arrangement of graphite sheets is suppressed. By controlling the amount of curing agent and solvent used to regulate the degree of polymerization, the graphitization amorphous degree of the hard carbon can be controlled, so that a large number of micropores are formed while having a certain structural stability. In addition, by doping with dopants, the interlayer spacing of the hard carbon can be widened, sodium ion insertion / extraction can be promoted, and defect sites can be introduced to increase sodium storage sites and improve the specific capacity of the negative electrode. Without sacrificing the rate performance, the effective sodium storage sites of the sodium negative electrode are increased to the greatest extent. At the same time, a negative electrode material with stable structure and low specific surface area is obtained through a secondary sintering process of heat treatment and high-temperature carbonization treatment, so that the prepared hard carbon negative electrode has high specific capacity and high rate performance, and solves the technical problems of poor reversible specific capacity and rate performance of existing hard carbon materials.

[0031] The invention also discloses a modified hard carbon material prepared by the preparation method, which has the advantages of stable structure and low specific surface area.

[0032] The present invention also discloses a sodium ion battery based on the modified hard carbon material. According to relevant experimental results, the prepared sodium ion battery has a reversible specific capacity of 395 mAh / g at 0.1C, a first coulombic efficiency of 85%, and a specific capacity of 282 mAh / g at 5C. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a comparison diagram of the charge and discharge curves of the sodium ion battery prepared in Example 2 of the present invention at current densities of 0.1C and 10C. DETAILED DESCRIPTION

[0034] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0035] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0036] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0037] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0038] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0039] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0040] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0041] Example 1

[0042] A method for preparing a modified hard carbon material comprises the following steps:

[0043] Weigh 40g of epoxy resin, 8g of hexamethylenetetramine, and 0.8g of manganese chloride, add them to 20g of isopropanol, stir evenly, and obtain a mixture; transfer the obtained mixture to a heating apparatus, and perform heating curing treatment at a curing temperature of 150°C and a curing time of 24h; crush the cured precursor, and pass it through a 150-mesh sieve to obtain a hard carbon precursor;

[0044] The hard carbon precursor was transferred to a crucible and heat treated in a nitrogen atmosphere at a temperature of 500°C, a heat treatment time of 12 h, and a heating rate of 5°C / min, followed by cooling; the cooled sample was subjected to a high-temperature carbonization treatment in a nitrogen atmosphere at a temperature of 1400°C, a heating rate of 5°C / min, and a carbonization time of 2 h, and then passed through a 300-mesh sieve to obtain a modified hard carbon material.

[0045] The modified hard carbon material prepared in Example 1 can be used to prepare a sodium ion battery negative electrode and a corresponding sodium ion battery, comprising the following steps:

[0046] The negative electrode active material (modified hard carbon material), conductive additive (super P) and binder (CMC) are configured in a mass ratio of 8:1:1, and are uniformly dispersed in deionized water by a rotary mixer to obtain a uniformly mixed negative electrode slurry;

[0047] The negative electrode slurry was coated on the copper foil with an automatic coating machine to a coating thickness of 150 μm, and then placed in a vacuum drying oven to dry and remove the solvent. After drying, the area coated with the slurry was cut into negative electrode sheets with a diameter of 12 mm using a manual cutting machine;

[0048] The prepared electrode sheet was transferred to a glove box filled with argon and assembled into a 2032 button half-cell, using a pure sodium sheet as the counter electrode and a glass fiber membrane as the separator. The electrolyte used was a diethylene glycol dimethyl ether (DIGLYME) solution containing 1M sodium hexafluorophosphate (NaPF6).

[0049] Example 2

[0050] A method for preparing a modified hard carbon material comprises the following steps:

[0051] Weigh 40 g of phenolic resin, 4 g of hexamethylenetetramine, and 0.4 g of manganese chloride, add them to 15 g of ethanol, stir evenly, and obtain a mixture; transfer the obtained mixture to a heating apparatus, and perform heating curing treatment at a curing temperature of 180° C. for 16 h; crush the cured precursor, and pass it through a 150-mesh sieve to obtain a hard carbon precursor;

[0052] The hard carbon precursor was transferred to a crucible and heat treated in a nitrogen atmosphere at a temperature of 600°C, a heat treatment time of 6 hours, and a heating rate of 3°C / min, followed by cooling; the cooled sample was subjected to a high-temperature carbonization treatment in a nitrogen atmosphere at a temperature of 1300°C, a heating rate of 5°C / min, and a carbonization time of 3 hours, and then passed through a 300-mesh sieve to obtain a modified hard carbon material.

[0053] The modified hard carbon material in Example 2 is used to prepare the negative electrode of the sodium ion battery, and the sodium ion battery is assembled in the same manner as in Example 1.

[0054] Example 3

[0055] A method for preparing a modified hard carbon material comprises the following steps:

[0056] Weigh 40g of phenolic epoxy resin, 2g of maleic anhydride, and 0.8g of phosphoric acid, add them to 10g of ethylene glycol, stir evenly, and obtain a mixture; transfer the obtained mixture to a heating instrument, and perform heating curing treatment at a curing temperature of 200°C and a curing time of 8h; crush the cured precursor, and pass it through a 150-mesh sieve to obtain a hard carbon precursor;

[0057] The hard carbon precursor was transferred to a crucible and heat treated in a nitrogen atmosphere at a temperature of 700°C, a heat treatment time of 4 hours, and a heating rate of 5°C / min, followed by cooling; the cooled sample was subjected to a high-temperature carbonization treatment in a nitrogen atmosphere at a temperature of 1200°C, a heating rate of 3°C / min, and a carbonization time of 3 hours, and then passed through a 300-mesh sieve to obtain a modified hard carbon material.

[0058] The modified hard carbon material in Example 3 is used to prepare the negative electrode of the sodium ion battery, and the sodium ion battery is assembled in the same manner as in Example 1.

[0059] Example 4

[0060] A method for preparing a modified hard carbon material comprises the following steps:

[0061] Weigh 40g of polyethylene resin, 8g of maleic anhydride, and 0.4g of phosphoric acid, add them to 20g of water, stir evenly, and obtain a mixture; transfer the obtained mixture to a heating apparatus, and perform heating curing treatment at a curing temperature of 220°C for a curing time of 6h; crush the cured precursor, and pass it through a 150-mesh sieve to obtain a hard carbon precursor;

[0062] The hard carbon precursor was transferred to a crucible and heat treated in a nitrogen atmosphere at a temperature of 600°C, a heat treatment time of 6 hours, and a heating rate of 5°C / min, followed by cooling; the cooled sample was subjected to a high-temperature carbonization treatment in a nitrogen atmosphere at a temperature of 1200°C, a heating rate of 2°C / min, and a carbonization time of 4 hours, and then passed through a 300-mesh sieve to obtain a modified hard carbon material.

[0063] The modified hard carbon material in Example 4 is used to prepare the negative electrode of the sodium ion battery, and the sodium ion battery is assembled in the same manner as in Example 1.

[0064] Example 5

[0065] A method for preparing a modified hard carbon material comprises the following steps:

[0066] Weigh 40g of urea-formaldehyde resin, 10g of maleic anhydride, and 0.2g of phosphoric acid into 5g of isopropanol, stir evenly, and obtain a mixture; transfer the obtained mixture to a heating apparatus, and perform heating curing treatment at a curing temperature of 200°C for 12h; crush the cured precursor, and pass it through a 150-mesh sieve to obtain a hard carbon precursor;

[0067] The hard carbon precursor was transferred to a crucible and heat treated in a nitrogen atmosphere at a temperature of 600°C, a heat treatment time of 6 hours, and a heating rate of 5°C / min, followed by cooling; the cooled sample was subjected to a high-temperature carbonization treatment in a nitrogen atmosphere at a temperature of 1300°C, a heating rate of 2°C / min, and a carbonization time of 2 hours, and then passed through a 300-mesh sieve to obtain a modified hard carbon material.

[0068] The modified hard carbon material in Example 5 is used to prepare the negative electrode of the sodium ion battery, and the sodium ion battery is assembled in the same manner as in Example 1.

[0069] Example 6

[0070] A method for preparing a modified hard carbon material comprises the following steps:

[0071] Weigh 40g of sugar alcohol resin, 4g of maleic anhydride, and 0.4g of boric acid, add them to 10g of water, stir evenly, and obtain a mixture; transfer the obtained mixture to a heating apparatus, and perform heating and curing treatment at a curing temperature of 180°C for 12h; crush the cured precursor, and pass it through a 150-mesh sieve to obtain a hard carbon precursor;

[0072] The hard carbon precursor was transferred to a crucible and heat treated in a nitrogen atmosphere at a temperature of 600°C, a heat treatment time of 6 hours, and a heating rate of 5°C / min, followed by cooling; the cooled sample was subjected to a high-temperature carbonization treatment in a nitrogen atmosphere at a temperature of 1400°C, a heating rate of 2°C / min, and a carbonization time of 1 hour, and then passed through a 300-mesh sieve to obtain a modified hard carbon material.

[0073] The modified hard carbon material in Example 6 is used to prepare the negative electrode of the sodium ion battery and assemble the sodium ion battery. The method is the same as that in Example 1, except that the mass ratio of the modified hard carbon material, the conductive additive and the binder is 8:4.5:0.5; the conductive additive is acetylene black and the binder is sodium carboxymethyl cellulose.

[0074] Example 7

[0075] A method for preparing a modified hard carbon material comprises the following steps:

[0076] Weigh 40g of polycarbonate, 4g of benzyldimethylamine, and 0.4g of phosphoric acid, add them to 10g of water, stir evenly, and obtain a mixture; transfer the obtained mixture to a heating apparatus, and perform heating curing treatment at a curing temperature of 120°C and a curing time of 24h; crush the cured precursor, and pass it through a 150-mesh sieve to obtain a hard carbon precursor;

[0077] The hard carbon precursor was transferred to a crucible and heat treated in a nitrogen atmosphere at a temperature of 400°C, a heat treatment time of 12 h, and a heating rate of 1°C / min, followed by cooling; the cooled sample was subjected to a high-temperature carbonization treatment in a nitrogen atmosphere at a temperature of 1000°C, a heating rate of 10°C / min, and a carbonization time of 8 h, and then passed through a 300-mesh sieve to obtain a modified hard carbon material.

[0078] Example 8

[0079] A method for preparing a modified hard carbon material comprises the following steps:

[0080] Weigh 40g of polyvinylidene fluoride, 10g of hexamethylenediamine, and 0.2g of silicon, add them to 5g of ethylene glycol, stir evenly, and obtain a mixture; transfer the obtained mixture to a heating apparatus, and perform heating curing treatment at a curing temperature of 220°C and a curing time of 1h; crush the cured precursor, and pass it through a 150-mesh sieve to obtain a hard carbon precursor;

[0081] The hard carbon precursor was transferred to a crucible and heat treated in a nitrogen atmosphere at a temperature of 800°C, a heat treatment time of 1 h, and a heating rate of 5°C / min, followed by cooling; the cooled sample was subjected to a high-temperature carbonization treatment in a nitrogen atmosphere at a temperature of 1700°C, a heating rate of 2°C / min, and a carbonization time of 2 h, and then passed through a 300-mesh sieve to obtain a modified hard carbon material.

[0082] Comparative Example 1

[0083] (1) Weigh 40 g of epoxy resin and 8 g of hexamethylenetetramine, add them to 20 g of isopropanol, and stir evenly;

[0084] (2) transferring the mixture to a heating apparatus for heating and curing at a temperature of 150° C. for 24 h;

[0085] (3) crushing the solidified precursor and passing it through a 150-mesh sieve to obtain a hard carbon precursor;

[0086] (4) transferring the crushed powder to a crucible and subjecting it to heat treatment in a nitrogen atmosphere at a temperature of 500°C, a heat treatment time of 12 h, and a heating rate of 5°C / min;

[0087] (5) The cooled sample was carbonized at high temperature in a nitrogen atmosphere at a temperature of 1600°C, a heating rate of 5°C / min, and a carbonization time of 2 h. The prepared hard carbon was sieved through a 300-mesh sieve to obtain a finished hard carbon.

[0088] (6) The hard carbon material is used to prepare the negative electrode of the sodium ion battery, and the sodium ion battery is assembled in the same manner as in Example 1.

[0089] Comparative Example 2

[0090] (1) Weigh 40 g of phenolic resin, 4 g of hexamethylenetetramine, and 0.4 g of manganese chloride, add them to 15 g of ethanol, and stir evenly;

[0091] (2) transferring the mixture to a heating apparatus for heating and curing at a curing temperature of 180° C. for 16 h;

[0092] (3) crushing the solidified precursor and passing it through a 150-mesh sieve to obtain a hard carbon precursor;

[0093] (4) The cooled sample was carbonized at high temperature in a nitrogen atmosphere at a temperature of 1300°C, a heating rate of 5°C / min, and a carbonization time of 3 h. The prepared hard carbon was sieved through a 300-mesh sieve to obtain a finished hard carbon.

[0094] (5) The hard carbon material is used to prepare the negative electrode of the sodium ion battery, and the sodium ion battery is assembled in the same manner as in Example 1.

[0095] Table 1 is the electrochemical performance test results obtained by Examples 1-4, Comparative Example 1 and Comparative Example 2. It can be seen that the introduction of doping elements can increase the sodium storage at defect sites, and the capacity is significantly improved, but the capacity of the introduced defective part belongs to irreversible capacity, so the coulombic efficiency in the first week is reduced. Compared with the hard carbon prepared by one-step calcination in Comparative Example 2, the reversible specific capacity and the first-week coulombic efficiency of the hard carbon negative electrode prepared by the two-step method are higher than those of the one-step method. At the same time, the specific capacity at 0.2C is also higher than that of the one-step method. This is because the pore size formed during the heat treatment of the one-step method is larger, the corresponding pore volume is larger, and thus the specific surface area is large, and some sodium ions are difficult to deintercalate after embedding, resulting in capacity loss, a decrease in reversible specific capacity, and low coulombic efficiency in the first week.

[0096] Table 1 Electrochemical performance test results of the samples prepared in Examples 1-4, Comparative Examples 1 and 2

[0097]

[0098]

[0099] Figure 1This is a comparison chart of the charge and discharge curves of the sodium ion battery prepared in Example 2 of the present invention at current densities of 0.1C and 5C. From the figure, it can be seen that the hard carbon prepared by this scheme can be used for the sodium ion battery with a reversible specific capacity of 0.1C to reach 395mAh / g, and the first coulombic efficiency is 85%. The specific capacity of 5C is 282mAh / g, and the capacity retention rate is 71.39%, which has excellent rate performance. This is due to the optimization of the resin precursor curing process, the preparation of a structurally stable resin precursor, and the resin-based hard carbon amorphous structure improves the ion transmission efficiency. At the same time, through solvent pore formation, it has more nanopores inside, providing additional sodium storage sites and improving the rate performance. Finally, with the appropriate heat treatment process, a lower specific surface area is obtained, the irreversible capacity loss is reduced, and the first week coulombic efficiency is improved.

[0100] By comparing the results of Comparative Example 1, Comparative Example 2 and Examples 1-4, it can be found that after doping and secondary carbonization of pre-carbonization and high-temperature carbonization, the hard carbon obtains a moderate interlayer spacing, which increases the effective sodium storage space without increasing the specific surface area of ​​the material. Therefore, the specific capacity and rate performance of the prepared sodium ion battery are significantly improved compared with the control sample.

[0101] The present invention uses organic matter as a precursor, and can form a cross-linked network structure by cross-linking and curing with a curing agent, and in the subsequent carbonization process, the directional arrangement of graphite sheets is suppressed. By regulating the degree of polymerization, the graphitization amorphous degree of hard carbon can be controlled, so that a large number of micropores are formed while having a certain structural stability. In addition, by doping, the interlayer spacing of hard carbon can be widened, sodium ion insertion / extraction can be promoted, and defect sites can be introduced to increase sodium storage sites and improve the specific capacity of the negative electrode. The hard carbon material prepared by the modification method provided by the present invention is used for the negative electrode of a sodium ion battery. The reversible specific capacity of the prepared sodium ion battery at 0.1C can reach 395mAh / g, the first coulomb efficiency reaches 85%, and the specific capacity of 5C is 282mAh / g. The carbon material provided by the present invention can effectively improve the specific capacity and rate performance of the negative electrode of a sodium ion battery, and the preparation method is simple and easy to operate, suitable for large-scale production, and has good practical prospects.

[0102] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a modified hard carbon material, characterized in that: The following steps are involved: After mixing the organic matter, the curing agent, the solvent and the dopant, the mixture is heated and cured to obtain a hard carbon precursor; The hard carbon precursor is subjected to heat treatment and high-temperature carbonization treatment in sequence to obtain a modified hard carbon material.

2. The method for preparing a modified hard carbon material according to claim 1, characterized in that: The organic matter is one or more of acrylic resin, phenolic resin, epoxy resin, furfural resin, urea-formaldehyde resin, sugar alcohol resin, polyurethane, polyethylene, polyvinyl chloride, polyvinyl chloride alcohol, polycarbonate, polytetrafluoroethylene, polyvinylidene fluoride, polyacrylonitrile, styrene-butadiene rubber, polyethylene oxide, polymethyl acrylate and polyimide.

3. The method for preparing a modified hard carbon material according to claim 1, characterized in that: The curing agent is one or more of hexamethylenetetramine, 2,4,6-tris(dimethylaminomethyl)phenol, benzyldimethylamine, maleic anhydride, bismaleic anhydride, hexamethylenediamine and metaphenylenediamine.

4. The method for preparing a modified hard carbon material according to claim 1, characterized in that: The solvent is one or more of water, isopropanol, ethanol, ethylene glycol, and n-butanol; The dopant is one or more of a metal element, a non-metal element, a metal compound and a non-metal compound; The metal element is one or more of copper, magnesium, manganese, tin, cobalt and nickel, and the non-metal element is one or more of silicon, sulfur, phosphorus and boron; the metal compound is one or more of tin oxide, cobalt oxide, nickel oxide, manganese oxide, sodium phosphate, sodium dihydrogen phosphate, tin acetate, tin chloride, manganese chloride, cobalt carbonate, copper hydroxide, cobalt hydroxide, tin hydroxide and nickel hydroxide; the non-metal compound is one or more of silicon dioxide, phosphorus pentoxide, boric acid, silicic acid, phosphoric acid, ammonium dihydrogen phosphate, ammonium phosphate and ammonium sulfate.

5. The method for preparing a modified hard carbon material according to claim 1, characterized in that: The mass ratio of the curing agent to the organic matter is 1:(1-20); the mass ratio of the solvent to the organic matter is 1:(1-8); the mass ratio of the dopant to the organic matter is 1:(20-500); The temperature of the heating and curing treatment is 120-220°C and the time is 1-24h; After the heating and curing, the product is screened to obtain a hard carbon precursor.

6. The method for preparing a modified hard carbon material according to claim 1, characterized in that: The heat treatment is carried out in an inert atmosphere; the temperature of the heat treatment is 400-800°C, the heating rate is 1-10°C / min, and the heat treatment time is 1-12h; The inert atmosphere is one of argon and nitrogen.

7. The method for preparing a modified hard carbon material according to claim 1, characterized in that: The heat treatment and the high-temperature carbonization treatment also include a grinding treatment; the temperature of the high-temperature carbonization treatment is 1000-1700°C, the heating rate is 1-10°C / min, and the duration of the high-temperature carbonization treatment is 1-8h.

8. A modified hard carbon material, characterized in that: The preparation method is described in any one of claims 1 to 7.

9. A sodium ion battery negative electrode material, characterized in that the sodium ion battery negative electrode material is obtained by coating a sodium ion battery negative electrode slurry obtained by mixing a modified hard carbon material, a conductive additive and a binder on a current collector and drying the mixture; The mass ratio of the modified hard carbon material, the conductive additive and the binder is 8:(1-4.5):(0.5-1); The conductive additive is one of Super P, acetylene black or Ketjen black; the adhesive is one of polyacrylic acid or sodium carboxymethyl cellulose.

10. A sodium ion battery, characterized in that: The negative electrode material of the sodium ion battery according to claim 9; the electrolyte of the sodium ion battery is composed of a sodium salt and an organic solvent; The sodium salt includes at least one of NaBF4, NaFSI, NaClO4, NaTFSI and NaPF6; The organic solvent includes at least one of ethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethyl carbonate, diethyl carbonate, propylene carbonate, and ethylene carbonate.

Citation Information

Patent Citations

  • Composite hard carbon cathode material of lithium ion battery and preparation method thereof

    CN101887966A

  • Phenolic resin / sucrose-based hard carbon microsphere material, preparation method thereof and sodium ion battery

    CN112125295A

  • Negative electrode material for lithium ion battery and preparation method of negative electrode material

    CN114249324A

  • Hard carbon material, preparation method thereof, electrode, battery and application

    CN114368739A